Investigating the anti-inflammatory and immune-modulatory effects of “Gola” guava fruit and leaf extract in alleviating papain-induced knee osteoarthritis - Shahid, Arashi; Inam-Ur-Raheem, Muhammad; Socol, Claudia Terezia; Maerescu, Cristina Maria; Criste, Florin Leontin; Murtaza, Hafiz Bilal; Bhat, Zuhaib F.; Hussain, Shahzad; Aadil, Rana Muhammad (Frontiers in Sustainable Food Systems, 2024)
This present research was designed to investigate the anti-inflammatory and immune-modulatory effects of a 50% hydroethanolic extract of "Gola" guava fruit (GF50%) and guava leaf (GL50%) against papain-induced knee osteoarthritis (KOA). Sixty Sprague Dawley rats were divided into five groups (10 rats/group): T0 (negative control), T1 (positive control), T2 (200 mg/kg GF50%), T3 (400 mg/kg GF50%), T4 (200 mg/kg GL50%), and T5 (400 mg/kg GL50%). Physical parameters were evaluated throughout the trial, while biochemical, histopathological, and radiographic analyses were performed at 0, 15, and 30 days. The histopathological and radiographic analyses were evaluated using the Osteoarthritis Research Society International score (OARSI) and Kellgren-Lawrence (KL) classification systems, respectively. The T1 group demonstrated a significant increase in knee diameter, confirming successful OA induction. The T5 group maintained a significantly lower body weight at day 30, and the T3 group exhibited the highest weight gain. The high dose of GL50% (400 mg/kg) effectively reduced knee inflammation and significantly downregulated the myeloperoxidase (MPO), interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). In contrast, it significantly (p<0.001) upregulated the serum and knee capsule tissue superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). In addition, histopathological and X-ray examinations also confirmed the chondroprotective potential of GL50% extract against OA.Consequently, 400 mg/kg GL50% exhibited anti-inflammatory and chondroprotective potential by lowering oxidative stress and pro-inflammatory cytokines, as well as elevating antioxidant status.These findings could provide a theoretical basis for understanding the mechanism and potential medicinal value of guava fruit and leaf in treating KOA.